Roles of nitrate recycling ratio in the A2/O-MBBR denitrifying phosphorus removal system for high-efficient wastewater treatment: Performance comparison, nutrient mechanism and potential evaluation - Zhang, Miao; Song, Tianxin; Zhu, Chenjie; Fan, Yajun; Soares, Ana; Gu, Xiaodan; Wu, Jun (Elsevier, 2020)
The long-term effect of nitrate recycling ratios (R = 100%–500%) on the denitrifying phosphorus removal (DPR) characteristics was studied in a novel two-sludge system, which coupled Anaerobic Anoxic Oxic (A2/O) with Moving Bed Biofilm Reactor (MBBR) for simultaneous nitrogen (N) and phosphorus (P) removals. During the 220 days’ operation, effluent COD (30.87–45.15 mg/L) can meet the discharge standard completely, but N and P removals were significantly affected by the R-value, including CODintra removal efficiency (CODintra-Re: 56.09–85.98%), TN removal (TN-Re: 52.06–80.50%), anaerobic PO43− release (PO43--An: 10.66–29.02 mg/L) and oxic PO43− absorption (PO43--O: 2.22–6.26 mg/L). Meanwhile, N and P displayed close correlation with the ΔPO43−/ΔNO3- ratio of 4.20–4.41 at R = 300%–400%, resulting in the high-efficient anoxic poly-β-hydroxyalkanoates (PHA) utilization (ΔPHAA: 64.88 mgCOD/gVSS). Based on the stoichiometry methodology, at R of 300%–400%, the percentages of phosphorus accumulation organisms (PAOs) and glycogen accumulating organisms (GAOs) contributed to ΔPHAAn (ΔGlyAn) were 71.7%, 28.3% (61.3%, 38.7%) in the anaerobic stage, respectively, while N denitrification rate (NDRA: 3.91–3.93 mg N/(gVSS·h)) and P uptake rate (PURA: 3.76–3.90 mg P/(gVSS·h)) reached the peak, suggesting superior DPR performance with higher contribution of denitrifying PAOs (DPAOs) (70%) than denitrifying GAOs (DGAOs) (30%) in the anoxic stage. Microbial community analysis showed that Accumulibacter (27.66–30.01%) was more enriched than Competibacter (13.41–14.34%) and was responsible for the improved C, N, P removals and DPR characteristics. For optimizing operation, the combined effect of nitrate recycling ratio with other process parameters especially economic evaluation should be considered
Keywords: Microbial community Optimizing operation; Stoichiometry methodology; Nitrate recycling ratio; Denitrifying phosphorus removal; A2/O - MBBR